2016
DOI: 10.1007/s13277-016-5003-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lung large cell neuroendocrine carcinoma

Abstract: Lung large cell neuroendocrine carcinoma (L-LCNEC) is a rare, aggressive, and difficult-to-treat tumor. It is classified as a neuroendocrine subtype of large cell lung carcinoma (LCLC) belonging to the non-small cell lung cancer (NSCLC) group, but it is also included in the neuroendocrine tumor (NET) group. Most of the available data related to its treatment derive from retrospective analyses or small case series. For patients with L-LCNEC, prognosis is generally very poor. In early stages (I-II-III), surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 82 publications
(102 reference statements)
0
46
0
Order By: Relevance
“…8 The role for adjuvant chemotherapy for stage I LCNEC after surgical resection remains unknown, and small-scale studies have yielded conflicting results. [9][10][11][12] Most of the studies have investigated platinum-based regimens. To our knowledge, only a single prospective adjuvant chemotherapy trial has been completed exclusively in patients with resected LCNEC; the results were suggestive of benefit from adjuvant cisplatin and etoposide.…”
Section: Introductionmentioning
confidence: 99%
“…8 The role for adjuvant chemotherapy for stage I LCNEC after surgical resection remains unknown, and small-scale studies have yielded conflicting results. [9][10][11][12] Most of the studies have investigated platinum-based regimens. To our knowledge, only a single prospective adjuvant chemotherapy trial has been completed exclusively in patients with resected LCNEC; the results were suggestive of benefit from adjuvant cisplatin and etoposide.…”
Section: Introductionmentioning
confidence: 99%
“…8,22,28 Since Travis et al first reported LCNEC in 1991, many authors have reported that LCNECs are aggressive tumors, and patients with these tumors have very poor prognoses. 8,12,17,19,22,23,28,29 Although LCNEC is categorized among the non-small cell lung carcinoma (NSCLC), the biological behavior of these tumors is very similar to that of small cell lung carcinoma (SCLC). Given the complex clinicopathological and biological features of LCNEC, there is controversy as to whether LCNEC should be treated according to NSCLC or SCLC protocols.…”
mentioning
confidence: 99%
“…We need more cases to understand these tumors and to evaluate treatment regimens such as molecular-based therapy methods. 9,10…”
Section: Discussionmentioning
confidence: 99%